The Position of Czechoslovakia in the World Economy (Czech Journal of International Relations, 1967)
If we are looking to build any country in the world economy, we must do this position to be followed in a double sense, in a formal sense and in an absolute sense. Formal status is determined by the socio-economic form or by the ruling type of industrial relations. The formal status of socialist countries is therefore equal to each other, whereas the formal status of countries joining the world system of capitalism may be unequal, for example, when it comes to the relationship between an economically developed country and an economically less developed country.It is also about the unequal formal status of the country in the relationship between a socialist country and a capitalist country. The absolute position of the country is determined by the economic level, or rather by the ratio of the economic levels of different countries. The absolute position of the country in the world economy therefore depends on the amount of social work (living and embodied) spent in a certain social form simple work, private work, capital etc. invested in the creation of the social product of the given country, calculated per inhabitant. In this sense, the position of countries in the world system of capitalism and socialism are mostly unequal.